Time-Dependent Reliability Assessment of a Continuous I-shaped Steel Beam Considering Corrosion Effects - Nguyen, S. M.; Phan, V. L.; Tran, N. L.; Nguyen, X. H.; Nguyen, T. H. (Engineering, Technology & Applied Science Research, 2022)
Among other fields, climate change has a great influence on metal corrosion that reduces the durability and reliability of steel structures. A time-dependent reliability analysis includes time-dependent climate scenarios and deterioration processes as well as random variables, material properties, and dimensions. The extent of corrosion damage is calculated by tracking the evolution of the corrosion process using Monte Carlo simulations. The current paper presents a time-dependent reliability assessment of a continuous I-shaped steel beam, considering the corrosion effects of climate change in Vietnam. The results showed that the safety probability of a continuous steel beam considering metal corrosion from the pristine to 100 years reduces from 96.77% to 63.08%. These findings can be used to assess and provide a cost-technical analysis of climate adaptation measures.